Association of estimated pulse wave velocity with all-cause mortality and cardiovascular mortality in obstructive sleep apnea patients: results from NHANES - Lin, Huizhong; Zheng, Huiyun; Lin, Tao; Chen, Lianglong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study aims to investigate the relationship between estimated pulse wave velocity (ePWV) and all-cause mortality (ACM) and cardiovascular mortality (CVM) in patients with obstructive sleep apnea (OSA).Method and resultsA cohort study was conducted using data from the NHANES database (2005–2008, 2015–2018), focusing on adults with OSA. ePWV was calculated based on age and mean blood pressure. A weighted Cox regression model analyzed the association of ePWV with ACM and CVM, while restricted cubic spline (RCS) curves visualized this relationship. Kaplan–Meier (KM) survival curves assessed survival across different ePWV groups.The study involved 10,071 OSA patients with an average age of 48.46 years, with a follow-up period ending in December 2019 (average follow-up time: 102.10 ± 2.34 months). Results showed that increased ePWV correlated with higher ACM [hazard ratio [HR]: 1.25, 95% confidence interval [CI]: 1.20–1.31] and CVM (HR: 1.28, 95% CI: 1.21–1.36). RCS curves indicated stable mortality risks at ePWV ≤ 8.1 m/s, with rapid increases beyond this threshold. KM curves demonstrated poorer survival outcomes for OSA patients with elevated ePWV.ConclusionElevated ePWV levels are linked to increased ACM and CVM in OSA patients, suggesting that monitoring ePWV could help mitigate these risks and promote healthier longevity in this population.